Investigating EFL university teachers’ classroom management competency - Muhammed, Karwan; Ahmed , Hussein (Humanities Journal of University of Zakho, 2023)
The current paper aims to investigate university EFL teachers’ classroom management competency. Classroom management is essential for establishing an atmosphere favorable to learning as it comprises the techniques and processes handled by teachers to create an atmosphere that encourages both teaching and learning. The paper focuses on three aspects of classroom management competency, namely establishing rapport with students, managing time, and controlling the class. To bring about the set aims, a 15-item Likert scale questionnaire was administered to a sample of 37 EFL university teachers at the Department of English Language at the University of Zakho, Nawroz University, and University of Duhok during the academic year 2021-2022. The collected data were analyzed using the one-sample t-test on SPSS software. The findings demonstrated that teachers were competent in establishing rapport with students and possessed the competency to manage time effectively and control the class successfully. It is expected that such findings would make EFL teachers insightful to cope and catch up with modern professional teaching competencies.